ANALISIS KESALAHAN SISWA KELAS XI SMA NEGERI 7 PALU DALAM MENYELESAIKAN SOAL FUNGSI KUADRAT - Rahmat; Gandung Sugita; Nurhayadi (Jurnal Elektronik Pendidikan Matematika Tadulako, 2022)
This research is a qualitative study that agrees to describe the types of errors made by students of class XI SMA Negeri 7 Palu in solving quadratic function questions. Data were collected by means of test and interview methods. The research subjects consisted of 2 students. The results showed that the students' misconceptions were: (1) Wrong to write down what was known and asked from the questions, it was shown that the subject did not write down what was known and was asked for the answer. (2) Wrong in determining the solution of the problem, it is shown that the subject made an error in substituting the values ​​a, b, and c in the formula and wrong in determining the factor of a quadratic function. (3) wrong in determining the final answer. (4) wrong in multiplying the value of a to the quadratic function formula. Principle errors that were made by students were: (1) students did not understand the concept and did not master the prerequisite material, students did not write the formula for the peak point and were wrong in determining the value of the peak point of a parabola, procedural errors made by students were: (1) Not writing what was known and asked from the questions, it is shown that the subject did not write down what was known and was asked for the answer. (2) an error in carrying out the operation, it was shown that the student was wrong in doing the questions given. (3) incomplete procedure error.